2007
DOI: 10.1248/bpb.30.508
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Characterization of 5-Hydroxytryptamine-Receptor Subtypes in Circular Muscle from the Rat Stomach

Abstract: It is generally accepted that gastric emptying is regulated by the coordination of the proximal and distal stomach motilities. 5-HT has proven to be an important mediator of gastrointestinal motility.1,2) The stimulation of 5-HT 1B/1D receptors induces gastric accommodation in humans 3) and dogs, 4) and delays gastric emptying in humans. 5,6) The blockade of 5-HT 3 receptors inhibits gastrointestinal motility in humans. 7) In addition, the stimulation of 5-HT 4 receptors elicits gastrointestinal contractile ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 41 publications
(60 reference statements)
2
28
0
Order By: Relevance
“…40,41 Animal studies have shown that fundic contraction and relaxation of the stomach are regulated by 5-HT via 5-HT2A and 5-HT2B receptors as reported in rats, 42 guinea pigs, 43 and chickens, 44 as well as in the antrum in dogs. 11,45 Stimulation of the 5-HT2 receptor in dogs induced lower esophageal sphincter contractions, which were later inhibited by cyproheptadine.…”
Section: Functional Dyspepsiamentioning
confidence: 97%
“…40,41 Animal studies have shown that fundic contraction and relaxation of the stomach are regulated by 5-HT via 5-HT2A and 5-HT2B receptors as reported in rats, 42 guinea pigs, 43 and chickens, 44 as well as in the antrum in dogs. 11,45 Stimulation of the 5-HT2 receptor in dogs induced lower esophageal sphincter contractions, which were later inhibited by cyproheptadine.…”
Section: Functional Dyspepsiamentioning
confidence: 97%
“…A number of studies have characterized 5-HT-induced muscle contraction or relaxation responses and enhanced secretion in the GI tract via a multiplicity of 5-HT receptor subtypes [5,[9][10][11][12][13]. For example, in ferrets, 5-HT1 and 5-HT3 receptors mediate contraction, whereas in piglets, 5-HT1 receptors mediate the contraction in the ileum.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in ferrets, 5-HT1 and 5-HT3 receptors mediate contraction, whereas in piglets, 5-HT1 receptors mediate the contraction in the ileum. In addition, 5-HT2 receptors mediate contraction and 5-HT4 receptors mediate relaxation in the rat stomach [11]. 5-HT1 and 5-HT2 receptors mediate contractions and 5-HT4 receptors mediate the relaxation in the ileum [5,12].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations